2020
DOI: 10.3390/en13184701
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Long-Term Acid Gas Sequestration and Its Prediction: A Unique Case Study

Abstract: A twenty-four-year on-going project of acid gas sequestration in a deep geological structure was subject to detailed modelling based upon a large set of geological, geophysical, and petrophysical data. The model was calibrated against available operational and monitoring data and used to determine basic characteristics of the sequestration process, such as fluid saturations and compositions, their variation in time due to fluid migrations, and the gas transition between free and aqueous phases. The simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Z Zhang and Agarwal 23 developed a numerical simulation with TOUGH2 simulator to determine the outcomes of CO 2 sequestration using water alternating gas (WAG) technique in an aquifer and showed that WAG is a reliable and risk-free (relative to gas injection) method since it reduces gas vertical migration. W Szott et al 24 used a compositional simulator to study and assess acid gas sequestration in an aquifer beneath a natural gas reservoir. The simulation was run for 24 years to obtain data for leakage risk evaluation and estimation of storage capacity.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Z Zhang and Agarwal 23 developed a numerical simulation with TOUGH2 simulator to determine the outcomes of CO 2 sequestration using water alternating gas (WAG) technique in an aquifer and showed that WAG is a reliable and risk-free (relative to gas injection) method since it reduces gas vertical migration. W Szott et al 24 used a compositional simulator to study and assess acid gas sequestration in an aquifer beneath a natural gas reservoir. The simulation was run for 24 years to obtain data for leakage risk evaluation and estimation of storage capacity.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…The analysed geological structure includes the natural gas field located in the southern part of the Pre-Sudetian Monocline, Poland [21]. It forms an anticline with two local uprisings.…”
Section: Structure Modellingmentioning
confidence: 99%
“…A simulation model of the structure was constructed and calibrated [21]. A geological model was generated based on standard input data including structural maps of the above listed formations.…”
Section: Structure Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Szott et al [6] develop a model for an ongoing project (24 years) for acid gas sequestration in a deep geological structure. The model is based on the available operational and monitoring data, and it can help determine the basic characteristics of the sequestration process.…”
Section: Introductionmentioning
confidence: 99%